Implementasi Penguatan Pendidikan Karakter Berbasis Kelas pada Peserta Didik SMP Negeri 2 Biak - Riana Puspita Sarie (Journal on Education, 2023)
The problem in this research is focused on the Implementation of Strengthening class-based character education according to Permendikbud Number 20 of 2018 article 6. The type of research used in this research is qualitative research. This research activity was carried out by means of interviews, observation and documentation. The type of qualitative data is data obtained from observations, interviews and documentation through school principals, vice principals, subject teachers, homeroom teachers and students. Based on the research conducted, it was found that SMP Negeri 2 Biak kota, which is a superior school in Biak-Numfor Regency with Accreditation A, has implemented the Implementation of Strengthening class-based character education, it only needs to be improved, this is indicated by facilities and infrastructure that must be equipped, more optimized as well as the professionalism of subject teachers in compiling and implementing the values of strengthening class-based character education (learning tools/RPP), it is important to maximize this evaluation, support from school management must be further improved, through collaboration with teachers and parents, as well as the consistency of subject teachers in implementing and evaluating the values of strengthening character education in the classroom. The conclusion in this study is that the efforts of teachers and school management in shaping the character of students in schools must be further improved through more adequate facilities and infrastructure, workshops and seminars attended by teachers as well as active school management in managing student talent and competency agendas. Routinely.